“¿Por que Luder?” A revista peronista Línea e a campanha presidencial argentina de 1983 - Borrelli, Marcelo; AAA (Revista de Historia Social y de las Mentalidades, 2026)
This article presents findings from an ongoing investigation into the Argentine political press during the so-called “transition” to democracy, between 1982 and 1983. In particular, it investigates the editorial treatment and journalistic coverage offered by the Peronist magazine Línea before the presidential election of October 30, 1983 in Argentina, which would mean the democratic return after the experience of the military dictatorship in power since March 1976. The period studied extends from mid-1982, after the announcement of the military government on the rules of functioning of the political parties and an electoral schedule, until the days after the results of the elections. A qualitative approach is followed, based on discursive analysis. Among the conclusions, it stands out that Línea assumed the intellectual role of rethinking the Peronist identity and stimulating party unity through antagonism with the dictatorship, a position that changed once the electoral competition was launched in 1983, when the differentiation moved towards the candidacy of the radical party, to which he extended the negative properties attributed to the military government. In relation to the internal Peronist election of its candidates, from a position of intellectual autonomy, it initially opted for restructuring from the grassroots through the direct vote of its authorities and candidates, remaining relatively equidistant in the conflictive process of determining the presidential formula; but, once resolved, he decidedly decided to accompany her with a proselytizing tone. Finally, given the Peronist defeat in the presidential election, the terms of the media's criticism of the party strategy and its own role in this regard are analyzed.
Keywords: imprensa; peronismo; transição; ditadura militar argentina; eleições na Argentina em 1983